Framework for Design Recommendations to Optimise Operational Dashboards in Supply Chain Management by Integrating Cognitive Neuroscience Principles - Magnus, Siv Merethe (Curtin University, 2025)
Designing intuitive dashboards for supply chains is vital for boosting transparency, efficiency, and productivity, ultimately leading to significant cost savings and substantial profits for businesses. In our research, we developed 30 key recommendations for designers to follow, when designing dashboards aimed at enhancing decision-making and streamlining operations. These guidelines make complex data accessible and actionable, empowering staff to respond swiftly to operational challenges. Our research insights will empower designers to build impactful dashboards that deliver measurable results in the supply chain sector.